MAHMUD YUNUS AND THE MODERNIST PARADIGM IN QUR’ANIC INTERPRETATION: A FOUNDATIONAL STUDY OF SCIENTIFIC EXEGESIS IN INDONESIA - Hamzah, Amir; Ni'mah, Siar; Firdaus, Firdaus (Universitas Nurul Jadid, 2025)
Tafsir Qur’an Karim by Mahmud Yunus is recognized as the first complete modern-style exegesis of the Qur’an in Indonesia. One of its notable approaches is the integration of scientific perspectives into the Qur’anic verses. This study aims to examine how Mahmud Yunus interprets verses of the Qur’an related to science. This research employs a qualitative library research method, using Tafsir Qur’an Karim as the primary source, alongside various books, and scholarly articles as a secondary sources. Data related to Mahmud Yunus’s scientific exegesis were collected from a specific section at the end of his tafsir titled Kesimpulan Isi Al-Qur’an, which features scientific themes, particularly verses concerning natural phenomena such as physics, chemistry, and earth sciences. Based on these themes, we conducted a close reading and analysis of his interpretation of relevant verses. The findings highlight two main points: (1) Mahmud Yunus engaged in scientific exegesis earlier than the commonly recognized introductory phase of the 1960s, positioning him as one of the pioneers of scientific exegesis in Indonesia; (2) his model of scientific exegesis includes references to scientific theories from European scientists, such as Newton and various astronomers, aiming to provide a broader explanation that strengthen faith, as illustrated in QS. Al-An’ām (6): 96. In several instances, he attempts to harmonize kawniyyah (cosmological) verses with scientific findings to highlight the miraculous nature of the Qur’an, as seen in QS. Al-Anbiyā’ (21): 30. Thus, his approach to scientific exegesis can be categorized as both apologetic and descriptive-informative, rather than theoretical critique.